Muslim employees’ religious and intersectional identities as sources of discrimination: how deeper understanding can improve managerial practice - Gottardello, Debora; Cascón-Pereira, Rosalía; Anderson, Deirdre (Emerald, 2025)
Purpose: This study aims to explore how intersecting identities shape experiences of workplace discrimination faced by Muslim employees in Catalonia, Spain. We seek to understand the interplay of religion, ethnicity, gender and age in their employment experiences in order to improve managerial practices. Design/methodology/approach: The research employs a qualitative approach, conducting in-depth interviews with 39 diverse Muslim employees in Catalonia through convenience and snowball sampling to support an intersectional analysis. Findings: Findings reveal that Muslim employees navigate a workplace environment where their experiences of discrimination are shaped by intersecting identities including religion, age, gender and ethnicity which become salient at various stages of their careers, prompted by HRM practices such as recruitment, selection and promotion. Their experiences as recipients of these practices illuminate the complex ways in which intersecting identities shape the experiences of discrimination. The study reveals the hiding of their religious identity, giving up on traditional career paths, seeking social support from other Muslims and emphasizing privileged identities, to deal with discrimination. Originality/value: This study deepens understanding of the complexity of religious identity in minorities and explores its role in workplace discrimination. In particular, the research sheds light on the psychological impact in the form of feelings of guilt and shame which arise from coping strategies such as concealing religious markers which are adopted by these employees in response to organizational and managerial practices. Lastly, the paper stresses the need for intersectional approaches in order to improve effectiveness of HR policies and managerial practices.
Keywords: 35 Commerce, Management, Tourism and Services; Business & Management; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; 5201 Applied and developmental psychology; Discrimination; cultural literacies; intersectionality; Muslim identity; religious identity; managerial practices